Ros Online Ordering System (ROOS) / Umiyatul Umairah Rafii - Rafii, Umiyatul Umairah (2017)
The project started by identifying the current processes and problems faced by Ros Kerepek Enterprise in their ordering process where the customer usually order through calls or Whatsapp. The problem was identified and the developer found the solution to reduce the problem is by developing Ros Online Ordering System. In order to start the project, a suitable method for development process have been chooses to build the system to achieve the project objective. An evaluation has been made by some users and experts to test the functionality and the usability of the system. The results from the user evaluation shows the highest means of 3.67 on efficiency, 3.67 on user interface, 3.64 on perceived usefulness, 3.6 on satisfaction, 3.45 on perceived ease of use and 3.42 on consistency. Overall, users were satisfied with the system that has been develop. Recommendations and suggestions received from the evaluation and would be used to improve and enhance the system in the future.